Prevalence of lung function disorder among healthcare workers who smoke in Tishreen university hospital - محمد الخيّر; مجد زيد (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Lung function can be affected by multiple factors, such as smoking, age, sex, height and weight. Aim of the study is determining the prevalence of smoking and lung function disorder in a pool of healthcare workers and determining the relationship between lung function disorder and age, sex, and body mass index (BMI), Methods: The study was conducted at the University Hospital of Latakia between 2019-2020 and involved 500 participants. After excluding non-smokers, the study included 277 individuals, the length and weight of each participant was measured, then the body mass index (BMI) was calculated, the question of age and years of smoking was questioned, and lung function was measured using the spirometry device in the standard way. Results: Smoking prevalence was (55.4%). The study contains (222 females, 55 males, average age: 47 years) of smokers The prevalence of lung function disorder among them was (7.3%), All cases are of an obstructive pattern. The study of the relationship between lung function disorder and age, sex, body mass index (BMI) shows a statistically significant positive relationship between lung function disorder and age (p-value = 0.002). It also found that there was a statistically significant relationship between sex and lung function disorder (p-value = 0.0001). As for the relationship with the body mass index (BMI) there was no statistically significant relationship between the disorder of lung function and the body mass index (BMI) (p-value = 0.05).